2012
DOI: 10.1007/s11104-012-1146-2
|View full text |Cite
|
Sign up to set email alerts
|

Alpine plant functional group responses to fertiliser addition depend on abiotic regime and community composition

Abstract: Background and aims We ask how productivity responses of alpine plant communities to increased nutrient availability can be predicted from abiotic regime and initial functional type composition. Methods We compared four Caucasian alpine plant communities (lichen heath, Festuca varia grassland, Geranium-Hedysarum meadow, snow bed community) forming a toposequence and contrasting in productivity and dominance structure for biomass responses to experimental fertilization (N, P, NP, Ca) and irrigation for 4-5 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
29
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 72 publications
7
29
1
Order By: Relevance
“…N addition increased the leaf length and the biomass of K. macrantha , P. viviparum and P. anserine at the wet site when neighbours were retained, indicating that these three species would be N limited in the studied communities and all of them should be N competitive. This is in line with other researchers, who found that the dominance of some sedge species in subalpine32 and alpine grassland33 and P. viviparum at polar semi-desert site34 was increased by N addition. Moreover, the positive effect of N addition on P. anserine might also be supported by the increased dominance of P. anserine in abandoned livestock enclosures (brush-ringed or fenced paddocks), where the soil is much richer in N content35.…”
Section: Discussionsupporting
confidence: 93%
“…N addition increased the leaf length and the biomass of K. macrantha , P. viviparum and P. anserine at the wet site when neighbours were retained, indicating that these three species would be N limited in the studied communities and all of them should be N competitive. This is in line with other researchers, who found that the dominance of some sedge species in subalpine32 and alpine grassland33 and P. viviparum at polar semi-desert site34 was increased by N addition. Moreover, the positive effect of N addition on P. anserine might also be supported by the increased dominance of P. anserine in abandoned livestock enclosures (brush-ringed or fenced paddocks), where the soil is much richer in N content35.…”
Section: Discussionsupporting
confidence: 93%
“…Within the sedges, both C. vaginata and C. bigelowii decreased in response to perturbations in the meadow community, while C. bigelowii initially increased, but then dramatically decreased in cover under nutrient amendment in the meadow. As has been documented previously, sedges and grasses differ significantly in their responses to fertilization in alpine and subalpine systems (Soudzilovskaia and Onipchenko 2005, Onipchenko et al 2012, Alatalo et al 2014. Our results add credence to the idea of separating the various subgroups of v www.esajournals.org graminoids instead of grouping them together at the functional group level, but even this may be insufficient to predict individual species responses.…”
Section: Lack Of Functional Group Fidelity In Responses To Perturbationsmentioning
confidence: 70%
“…grasses, forbs, legumes and sedges), can influence the direction and magnitude of the changes to N addition (e.g. Tilman et al ., ; Bassin et al ., ; Marquard et al ., ; Bai et al ., ; Onipchenko et al ., ). Grasses are generally favoured by N addition, while legumes are not, and forb responses tend to be species specific (Theodose & Bowman, ; Leto et al ., ; Niu et al ., ; Duprè et al ., ).…”
Section: Introductionmentioning
confidence: 99%